Involvement of Calcium and Calmodulin in Nitric Oxide-Regulated Senescence of Cut Lily Flowers - Zhang, Jing; Fang, Hua; Huo, Jianqiang; Huang, Dengjing; Wang, Bo; Liao, Weibiao (Frontiers in Plant Science, 2018)
Both nitric oxide (NO) and calcium ion (Ca2+)/calmodulin (CaM) have been shown to regulate the senescence of cut flowers. However, not much is known about the crosstalk between NO and Ca2+/CaM during the senescence of cut flowers. In this study, cut Oriental × Trumpet hybrid lily “Manissa” were used to investigate the roles and relationship between NO and Ca2+/CaM during postharvest freshness. The results show that the effects of CaCl2 or NO donor SNAP on the vase life, maximum flower diameter and hours until full opening were dose-dependent, with an optimum concentration of 20 mM CaCl2 or 100 μM SNAP. However, Ca2+ chelators EGTA or BAPTA/AM, Ca2+ channel inhibitors LaCl3 or nifedipine and CaM antagonists W-7 or TFP inhibited the promotion of SNAP. SNAP applied alone significantly increased the endogenous Ca2+/CaM contents in cut lily flowers, while EGTA, BAPTA/AM, LaCl3, nifedipine, W-7, and TFP decreased the advancement of SNAP. In addition, the SNAP-induced Ca2+-ATPase activity was more than twice as much as the control, but EGTA, BAPTA/AM, LaCl3, nifedipine, W-7, and TFP also reversed the enhancement. Moreover, EGTA, BAPTA/AM, LaCl3, nifedipine, W-7, and TFP prevented the SNAP-induced upregulation of gene expression of CaM, CBL1, and CBL3, which is associated with calcium signaling pathway. Overall, these results suggest that Ca2+/CaM may function as downstream molecules in NO-regulated senescence of cut flowers.